2022
DOI: 10.3390/ijerph19063396
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-21 Expression as a Prognostic Biomarker in Oral Cancer: Systematic Review and Meta-Analysis

Abstract: Oral carcinoma represents one of the main carcinomas of the head and neck region, with a 5-year survival rate of less than 50%. Smoking and tobacco use are recognized risk factors. Prognostic survival biomarkers can be a valid tool for assessing a patient’s life expectancy and directing therapy towards specific targets. Among the biomarkers, the alteration of miR-21 expression in tumor tissues is increasingly reported as a valid prognostic biomarker of survival for oral cancer. The purpose of this meta-analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 50 publications
1
20
0
1
Order By: Relevance
“…Several reports suggested that enhanced expression of miR-21 is associated with the poor overall survival rate in OSCC patients (13, 14). Hence to ascertain whether miR-1307-5p exhibited potential as a prognosticator, we conducted survival analysis of miR-21-5p with miR-1307-5p using their normalised expression value from TCGA datasets and literature survey (205 OSCC patients).…”
Section: Resultsmentioning
confidence: 99%
“…Several reports suggested that enhanced expression of miR-21 is associated with the poor overall survival rate in OSCC patients (13, 14). Hence to ascertain whether miR-1307-5p exhibited potential as a prognosticator, we conducted survival analysis of miR-21-5p with miR-1307-5p using their normalised expression value from TCGA datasets and literature survey (205 OSCC patients).…”
Section: Resultsmentioning
confidence: 99%
“…The systematic review protocol has been registered on the INPLASY platform with registration number INPLASY2022110098 and DOI number 10.37766/inplasy2022.11.0098. The review was conducted following the guidelines of the Cochrane handbook, and the writing of the manuscript followed the indications of the PRISMA [ 11 , 12 , 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…Many miR have shown prognostic survival capabilities with potential as a biomarker. In the head and neck area, the main miR associated with a potential biomarker is miR-21 [ 18 ], which would be upregulated in tumor tissues whose overexpression is potentially associated with a worsening of prognosis; similarly, other upregulated miRs have also been investigated, and among these, the miR-31 [ 19 ] and miR-155 [ 20 ], among the downregulated miRs, the focus has mainly on the Let-7 microRNA family. Recently, some interesting studies have turned toward miR-195, which would be downregulated in the tissues of many cancers including bladder cancer, breast, stomach, lung, bone, and liver.…”
Section: Introductionmentioning
confidence: 99%